2017
DOI: 10.18632/oncotarget.16585
|View full text |Cite
|
Sign up to set email alerts
|

GALNT6 expression enhances aggressive phenotypes of ovarian cancer cells by regulating EGFR activity

Abstract: Ovarian cancer is the most lethal of the gynecologic malignancies. N-acetylgalactosaminyltransferase 6 (GALNT6), an enzyme that mediates the initial step of mucin type-O glycosylation, has been reported to regulate mammary carcinogenesis. However, the expression and role of GALNT6 in ovarian cancer are still unclear. Here we showed that high GALNT6 expression correlates with increased recurrence, lymph node metastasis, and chemoresistance in ovarian endometrioid and clear cell carcinomas; and higher GALNT6 lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…However, an inhibitory rather than an activatory effect on EGFR signaling has been reported for NEU1 overexpression in airway cells [ 114 ]. The O -glycosylation of EGFR, mediated by GALNT2 or GALNT6, two of the 20 GalNAc transferases catalyzing the first step in O -linked biosynthesis ( Table 1 ), results in enhanced malignancy of oral [ 64 ] and ovarian cancer [ 65 ], respectively. On the other hand, GALNT2 modification of EGFR reduces malignancy of hepatocarcinoma [ 66 ].…”
Section: How Glycosylation Modulates the Activity Of Specific Recementioning
confidence: 99%
“…However, an inhibitory rather than an activatory effect on EGFR signaling has been reported for NEU1 overexpression in airway cells [ 114 ]. The O -glycosylation of EGFR, mediated by GALNT2 or GALNT6, two of the 20 GalNAc transferases catalyzing the first step in O -linked biosynthesis ( Table 1 ), results in enhanced malignancy of oral [ 64 ] and ovarian cancer [ 65 ], respectively. On the other hand, GALNT2 modification of EGFR reduces malignancy of hepatocarcinoma [ 66 ].…”
Section: How Glycosylation Modulates the Activity Of Specific Recementioning
confidence: 99%
“…We also found that GALNT6 could bind to the ATPase domain of GRP78 and stabilizes the GRP78 protein through O-glycosylations, which also contributed to proper subcellular localization and antiapoptotic function of GRP78 protein in cancer cells [28] . EGFR was also shown to be a substrate of GALNT6 in ovarian cancer cells [15] .…”
Section: Discussionmentioning
confidence: 97%
“…We also found its upregulation in pancreatic cancer cells, in which GALNT6 could cause a cadherin switch (from E-cadherin to P-cadherin) affecting cellular adhesion to the underlying matrix [14] . High GALNT6 expression was also reported to be correlated with an increased risk of recurrence, lymph node metastasis, and chemoresistance in ovarian cancer [15] . It was also shown that GALNT6 was highly upregulated in colon adenocarcinomas compared with adjacent colon tissues, implying its important role in colon carcinogenesis [8] .…”
Section: Introductionmentioning
confidence: 95%
“…The high level of expression in the Basal and PMSG stages suggests that JAML might have a role in preantral follicles, especially in GC-GC or GC-oocyte interactions. GALNT6 has been shown to be essential for the activation of EGFR by phosphorylation and by modification of O-glycosylation (Lin et al, 2017). It is well known that LH-induced EGFR signaling plays a critical role in preovulatory follicle development by activating MAPK pathways and inducing the steroidogenic enzymes (Jamnongjit et al, 2005;Panigone et al, 2008;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%